TADWIN HADIS DAN KONTRIBUSINYA DALAM PERKEMBANGAN HISTORIOGRAFI ISLAM - Saifuddin, Saifuddin (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2013)
Historically, the process of tadwîn was through by the phases of a long and complex historical and colored many controversies. The controversy intensified when considering stream factor in it. Three traditional currents in Islam, Ahl al - Sunnah wa al - Jamaah, Shiites, and Kharijites, proved to have a history of their own tadwîn traditions were different from each other. Concurrently with the tadwîn process of hadith, the scholars also put its methodological tools. Methodological tools that in turn give effect to other disciplines, including Islamic historiography. This study tried to discover more about the dynamics that occured in the tadwîn tradition process and to what extent it impacted to the Islamic historiography. Through the method of historical - comparative historical or combined with Usul al - hadîts, this study revealead that the hadith tadwîn basically been going on since the period of the Prophet and continued in subsequent periods until finally composed